PERAN AHLI JIWA DALAM PEMBUKTIAN TINDAK PIDANA KEKERASAN PSIKIS DALAM RUMAH TANGGA - Ohoiwutun, Y A Triana; Nugroho, Fiska Maulidian; Samsudi, Samsudi; Dewanto, Ari (Veritas et Justitia, 2022)
Domestic psychic violence can be experienced by everyone, including children, wives, husbands, and others. As a material offense on domestic psychic violence, the elements resulting from psychological trauma must be proven. Therefore, the intervention of forensic psychologists and forensic psychiatrists is very important in cases of domestic psychic violence. The differences in the competence of psychologists and psychiatrists as well as the prospective roles of both professions in proving cases are the focus of the problems being studied. A normative legal research method with descriptive qualitative data analysis was employed in this research. The results showed that the existence of forensic psychologists and forensic psychiatrists is very important for finding material truths that can be scientifically tested in cases of domestic psychic violence. As evidence for letters and/or expert reports, the assessment results of forensic psychologists and forensic psychiatrists have accurate evidentiary value in forming a judge's conviction. This paper ends with a recommendation that as a form of protection for domestic violence victims, the role of psychologists and/or psychiatrists should be optimized, both in the pre-adjudication, and adjudication phases. In addition, considering the balanced position between psychologists and psychiatrists in law enforcement, this should not create jealousy and unhealthy competition between the two professions.